2020
DOI: 10.1177/0894486520967832
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Family Firm CEO Traditionality on Successor Choice: The Moderating Role of Socioemotional Wealth

Abstract: Drawing on upper echelons theory, this study examines how the traditionality of family chief executive officers (CEOs) influences the selection of their successors, and how this relationship is moderated by two dimensions of socioemotional wealth. Recognizing the central role of CEOs in determining successors, we show that a family CEO’s cultural values regarding traditionality have a significant positive effect on the probability that a family member is chosen as successor. We find that this relationship is s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 147 publications
(246 reference statements)
2
29
0
1
Order By: Relevance
“…Therefore, we contend that understanding the relation between family female directors and family SMEs' innovation intensity requires considering the contingency effect of the SEW dimensions in terms of appraisal of SEW preferences, by looking at the potential SEW losses and gains (Lu, Kwan, & Zhu, 2020; Samara et al, 2019; Vandekerkhof et al, 2015). Although considered essential to studying family firm behavior, family business scholars often treat SEW as an umbrella construct, failing to fully capture its multidimensionality (Swab et al, 2020) and related contingency effects (e.g., Vandekerkhof et al, 2015).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, we contend that understanding the relation between family female directors and family SMEs' innovation intensity requires considering the contingency effect of the SEW dimensions in terms of appraisal of SEW preferences, by looking at the potential SEW losses and gains (Lu, Kwan, & Zhu, 2020; Samara et al, 2019; Vandekerkhof et al, 2015). Although considered essential to studying family firm behavior, family business scholars often treat SEW as an umbrella construct, failing to fully capture its multidimensionality (Swab et al, 2020) and related contingency effects (e.g., Vandekerkhof et al, 2015).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…In this case, the time horizon in the family SME's decision‐making process spans generations and affects investments that may be bequeathed to descendants (Berrone et al, 2012), generating patient capital (Sirmon & Hitt, 2003, p. 343). Therefore, transgenerational aspirations lead family owners to consider their firm as not merely an asset, but a representation of their hopes for the future (Lu et al, 2020). The long‐term vision and planning horizon characterizing SEW preferences in terms of the family dynasty dimension are thus likely to shape the extent to which the board involving family female directors makes innovation decisions oriented toward the SME's future sustainability and competitiveness (Cennamo et al, 2012).…”
Section: Theoretical Background and Hypotheses Developmentmentioning
confidence: 99%
“…They have the merit of showing that psychological issues are crucial in defining strategic and governance choices regarding succession in family firms. Lu, Kwan, and Zhu (2020) explore the relationship between CEO traditionality and the probability that a family member is chosen as successor. Arguably, this paper considers the moderating role of family members' identification and sense of dynasty in the aforementioned relation.…”
Section: The Articles In This Second Special Issuementioning
confidence: 99%
“…Most studies conducted in specific contexts of countries, for example, the US or China, adopted standardized measurement items (e. g., Berrone et al, 2012), rather than developing contextualized items and findings. One study discussing succession at family firms in China used traditionality as its key independent variable, with two dimensions of SEW as moderators, and found that these moderators have a divergent impact on the likelihood of a family insider being chosen as successor; this gives some indication that SEW might not be so straightforward in Confucian societies (Lu, Kwan, & Zhu, 2021). Those specific countries were only used as contexts for data collection, rather than for the theoretical development of SEW in different cultures.…”
Section: Challenges and Current Issues Of Sewmentioning
confidence: 99%